PENGARUH CELEBRITY ENDORSER, BRAND IMAGE, WORD OF MOUTH, KUALITAS WEBSITE, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TOKOPEDIA - Muhani; Hanum San Sabillah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of Celebrity Endorser, Brand Image, Word of Mouth, Website Quality, and Price Perception on Purchase Decisions on E-commerce Tokopedia. The population in this study were all people of DKI Jakarta Province who shopped at Tokopedia. The results showed that Celebrity Endorser, Brand Image, Word of Mouth, Website Quality, and Price Perception had a positive and significant effect on Purchase Decisions on E-commerce Tokopedia.